1998
DOI: 10.1038/sj.onc.1202003
|View full text |Cite
|
Sign up to set email alerts
|

The BRCA2 is a histone acetyltransferase

Abstract: Patients carrying mutations in BRCA1 or BRCA2 tumor suppressor genes have shown to have high risk in developing breast and ovarian cancers. Two potential functions of BRCA2 were proposed which includes role in the regulation of transcription and also in DNA repair. Forty-®ve-amino acid region encoded by exon 3 of BRCA2 was shown to have transcriptional activation function. Recent studies of the several enzymes involved in acetylation and deacetylation of histone residues have revealed a possible relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 18 publications
0
50
0
1
Order By: Relevance
“…A role for BRCA1 in TCR is consistent with its ability to recruit transcriptional cofactors and regulate transcription (''Regulation of Transcription''). Interestingly, a histone acetyltransferase (HAT) enzymatic function was mapped to the N-terminus of BRCA2 (Siddique et al, 1998). Although the BRCA1 C-terminus can recruit histone deacetylases (Yarden and Brody, 1998), it is not clear whether BRCA1 can directly regulate histone acetylation.…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 99%
“…A role for BRCA1 in TCR is consistent with its ability to recruit transcriptional cofactors and regulate transcription (''Regulation of Transcription''). Interestingly, a histone acetyltransferase (HAT) enzymatic function was mapped to the N-terminus of BRCA2 (Siddique et al, 1998). Although the BRCA1 C-terminus can recruit histone deacetylases (Yarden and Brody, 1998), it is not clear whether BRCA1 can directly regulate histone acetylation.…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 99%
“…Previously we have shown that human Fli-1 and its related erg-2, erg-3 proteins act as sequence-speci®c transcriptional activators Siddique et al, 1993;Rao et al, 1993;Prasad et al, 1994). Here, we tested whether Fli-1b which lacks the ®rst exon can also act as a transcriptional activator.…”
Section: Human Fli-1b Functions As Sequence-speci®c Transcriptional Amentioning
confidence: 99%
“…Molecular characterization of these Ewing family of tumors revealed fusion of the EWS gene on chromosome 22, with either Fli-1 or erg genes located on chromosomes 11 and 21 respectively. Previously Fli-1 and Erg genes have been cloned by us and others (Ben-David et al, 1991;Prasad et al, 1992;Reddy et al, 1987) and the functional analysis of these proteins revealed that these proteins code for sequence-speci®c transcriptional activators with two transactivation domains present at amino-and carboxy-termini (Siddique et al, 1993;Rao et al, 1993). We and others have shown that EWS-Fli-1 and EWS-erg proteins encode transcriptional activators Baily et al, 1994) and these aberrant proteins show altered DNA binding and transactivation properties compared to normal Fli-1 and erg proteins.…”
Section: Introductionmentioning
confidence: 99%
“…During the preparation of this manuscript, Siddique et al (1998) reported that the BRCA2 is itself a histone acetyltransferase. These authors described that this activity maps to an N-terminal region of BRCA2 Figure 3 BRCA2 amino-terminus binds HAT activity in a P/ CAF-dependent manner.…”
mentioning
confidence: 99%